The concept of Will between Schopenhauer and Nietzsche (Damascus University Journal of arts and humanities sciences, 2021)
The concept of will in all its forms and types occupied a vital status in the history of philosophical thought, from Greek philosophy to modern and contemporary philosophy. This study addresses two German philosophers, Arthur Schopenhauer and Friedrich Nietzsche, challenged this concept, each from his perspective. No doubt, plenty of extended research is required should we liked to compare the two philosophers. However, we will try, as much as possible, to identify the most important ideas that form the compass of our research, especially with regard to our basic concept in this research, the will. Accordingly, we are going to clarify this concept, which takes the pattern of will of life in Schopenhauer, while taking the pattern of will of power in Nietzsche. We will see how these concepts form opposing visions after we have seen and discussed how this concept can be understood by both parties. All that after establishing the nature of will according to each of them and determining its relationship with the body, mind and knowledge. We will explain Nietzsche's critique of Schopenhauer’s concept of the will of life, and how Nietzsche benefited in his basic idea: will of power, from his predecessor Schopenhauer and was influenced by his idea after overcoming that influence in order to define how he established and employed Schopenhauer’s concept in a new distinct vision that reflects his philosophical creativity.
Keywords: The concept of Will between Schopenhauer and Nietzsche